An analysis of urban housing problems in Jabalpur city - Prashant Tiwari; Janki Prasad (National Geographical Journal of India, 2021)
Housing is one of the fundamental needs of people to provide social safety to people. The shortage of houses, dilapidated housing conditions, and homelessness are the fundamental problems in urban India. Jabalpur city is not an exception. The primary reason behind the housing problem is the unprecedented growth of population, exorbitant land prices, and lack of affordability among the city dwellers. The present study deals with housing aspects such as housing condition, typology, household size, ownership status, number of rooms, and toilet facility in the premises. The study is based on the primary household's survey and the data collected from 600 households covering all 15 administrative zones. The forty households surveyed with an interview schedule for each zone. The study reveals poor housing conditions in the old settled parts of the city, inhabited by socially and economically deprived sections and the slum localities. This study is helpful for the researchers of urban studies and the policymakers of urban development